Tales of king arthur - Brooks, Felicity; Matthews, Rodney (Usborne London, 2006)
A collection of faithful retellings of the classic stories of King Arthur and his Knights of the Round Table, from the sword in the stone to the last battle. Includes notes on both the author and the original text. Ideal for encouraging young readers to pursue an interest in literature